Identity Theft In Peer-To-Peer Lending Platform - Ika Oktaviana Dewi; Imam Wahyudi; Nanang Setiawan (ADPEBI, 2024)
This research aims to determine the mode of data theft in the pinjol or peer to peer lending platform. Peer to peer lending became popular during the pandemic and is an alternative to fulfill temporary financial needs due to the access and convenience offered by fintech providers, so that people prefer fintech over other financial entities. The method used in writing this article is a literature study of identity theft on peer to peer lending platforms. The main data in the library study method is secondary data sourced from books, the internet, articles, laws and other documents related to this research. The research results show that with the emergence of fintech as a manifestation of the industrial revolution 4.0, especially during the pandemic, fintech is using this opportunity to expand its scope by involving more customers. However, the difficulty for customers or fintech users to differentiate between legitimate and illegal loans provides opportunities for illegal loans to exploit as many victims as possible. One of the modus operandi of illegal loans is to insert spyware through smartphone access permits, which are then used to register or apply for financing with loans